PENGARUH IKLAN TELEVISI TERHADAP MINAT BELI SMARTPHONE PADA MASYARAKAT (STUDI KASUS DI KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT) - Hidayati, Rahma; Sudarman, sudarman; mustafa, mustafa (Universitas Teuku Umar, 2017)
Advertising smartphone is one factor very important in introducing a product to consumers. Foradvertising can affect mindset for consumers to use the offered by companies smartphone. Thisreport aims to understand analyze the influence of advertising smartphone in television stations ofinterest in buying the community in Sub District Johan Pahlawan District of Aceh West. This studyadopted qualitative approaches to explain data research obtained by using interviewing 10 sourceswho vote with used technique purposive sampling. According to the research has been discoveredthat viewing Any impact advertising smartphone presented on television stations of interest inbuying the community in Sub District Johan Pahlawan District of Aceh West. From the results ofresearch that has been done, can be stated that the impressions of smartphone ads can affectpeople's buying interest.Keywords: Advertising, Television, Interest, Smartphone